Soil nitrate, phosphorus and potassium concentration after four years of liquid swine manure application on Tifton 85 - Tangriani Simioni Assmann, Alceu Luiz Assmann , Laércio Ricardo Sartor, Talyta Zortéa1 (African Journal of Pig Farming, 2023)
One major problem of swine production is the huge volume of manure generated; this involve difficulties in proper handling of the residue when applied to the soil, given that such elements can be toxic to the environment. This study examined the vertical movement of the P, K and mineral N in the soil profile cultivated with Cynodon dactylon cv. Tifton 85 which was submitted consecutively to rates of Liquid Swine Manure (LSM) application (four years). The experiment was done using a randomized block design with four replications in a split-plot arrangement, where the whole plots were semiannual applications (November, 2002 to September, 2006) of increasing levels of LSM (0, 30, 60, 90, 120 and 180 m 3 ha-1 ); while the sub-plots were the soil samples at different depths (0-10, 10-20, 20-40, and 40-60 cm). The N-NO3 - leaching was observed when application of LSM exceeded 90 m3 ha-1 twice annually or during the year, suggesting a limit level for fertilizer on Tifton 85 pastures. Phosphorous and potassium accumulation was observed at higher LSM rate, mainly at the 0-10 cm soil layer since the soil P levels increased up to the highest evaluated depth at the 180 m3 ha-1 LSM level. LSM meets the Tifton 85 nutritional requirement regarding N, P and K when applied semi-annually at the rate of 90 m³ ha-1 without causing pollution effects; although the grass production responds up to 180 m3 ha-1 levels